Developing alternative modalities in public-private-people partnership for managing tourism in protected areas the case of Bataan Natural Park - Cordova, Lorenzo V. (School of Urban and Regional Planning, University of the Philippines Diliman, 2018)
The Philippines is one of the eighteen (18) megadiverse countries and has been losing its biodiversity at an unprecedented scale. The protected areas, being the last bastion of biodiversity for future generations, are necessitated to have new planning and management approaches. The Philippine Government initiated the Ecotourism Public-Private Partnership (PPP) Development, selecting three (3) protected areas to be model sites. This includes the Bataan Natural Park (BNP). The main objective was to attain partnership in tourism development that is economically attractive, environmentally friendly and sustainable, and socially equitable. The study examined the proposed Ecotourism PPP Development concept and how it progressed in BNP, its potential; and possible modalities as a mechanism to help in the implementation of ecotourism plans. The study also explored the possibility of the integration of "people" (partner community organization) into PPP to establish Public-Private-People Partnership (4P) approach for tourism development in the proposed sites along with adjacent areas. Furthermore, the study identified the possible scope/ roles of the public and private sector, and people in tourism 4P implementation in BNP. The current private sector engagement for tourism in BNP falls short in meeting the descriptors of a public-private partnership as defined by the Department of Environment and Natural Resources-Biodiversity Management Bureau (DENR-BMB). There is no existing engagement between Special Use Agreement in Protected Areas (SAPA)/MOA holders and the community partners of the Protected Area Management Board (PAMB) for ecotourism development. There is, however, a potential to move Tourism 4P, given the interest of all parties and the enabling policy environment at the national and local levels such as the Build-Operate-Transfer (BOT) Law, Public-Private Partnership for the People Initiative for Local Governments (LGU P4), and local PPP Codes. Tourism 4P can be undertaken via a joint venture agreement with the following options for partnership: Option 1 would be the partnership among DENR, private sector, and community. Option 2, on the other hand, added the LGU to the partners, particularly, the LGU's of Bagac and Orani. A key feature of Tourism 4P is the inclusion of the community from the design stage of implementation. It is recognized that the community has a key role to play in various tourism segments. Given limited financial capital, sweat equity and other non-cash contributions may serve as the community's equity in the joint venture. The method of valuation may be agreed upon by the involved parties. Tourism 4P in BNP has the potential to relieve the government from the financial and management burden. It is envisaged to increase government flexibility in channeling limited allocations to non-commercially viable Protected Areas (PAs) with high biodiversity importance. In general, a partnership in the income-generation aspect makes a good business sense. While the constitutional, legal, and policy framework are available to support Tourism 4P in PAs, specific regulations may be necessary for the proper guidance of the DENR in engaging interested private sector entities in PA management. This ensures that commercial development remains consistent with the PA's primary purpose of biodiversity conservation. Equally important is that the scope and limits of a 4P must be clearly defined. These can be addressed through a DENR administrative issuance on integrated or co-located projects and large- scale 4Ps in PAs.